Basic Science Techniques in Clinical Practice - Patel, H. R. H.; Arya, M.; Shergill, I. S.; SpringerLink (Online service) (London : Springer London, 2007)
Medical researchers including doctors, nurses, medical students and allied health professionals are required to undertake a period of research as part of their career pathway. Basic Science Techniques in Clinical Practice covers the main areas, allowing anyone to set up and complete research projects and this information can easily be translated to clinical projects. Written by international authors to provide a flavor from many institutions, the book$1 (Bs appeal is cross-sectional, both at hospital and primary care levels worldwide. The book covers modern laboratory techniques for laboratory-based research, as well as research governance and designing projects. The final sections importantly tackles data analysis and the presentation of the results (oral and written). This book is valuable reading for all doctors, medical students, and individuals in related specialities, either in research or considering research (e.g. MD, PhD, MSc and Intercalated BSc).s
Research Governance -- Designing Health Studies -- Immunohistochemistry -- Cell Culturing: A Beginner$1 (Bs Guide to Understanding the Basics of Cell Culturing -- Flow Cytometry -- Western, Northern, and Southern Blotting -- Fluorescent In Situ Hybridization -- Quantitative Reverse Transcriptase Polymerase Chain Reaction -- Proteonomics: High-Throughput Structural Biology$1 (BMethods for Cloning, Protein Expression, and Purification -- DNA and Tissue Microarrays -- Basic Scientific Techniques in Recording Cellular Data -- Presenting and Publishing Research Data -- Analyzing Health Studies -- Future.s
Keywords: Medicine; Laboratory medicine; Health informatics; Nursing administration; Medicine & Public Health; Health Informatics; Laboratory Medicine; Nursing Management/Nursing Research; Electronic books